AIS Revolutionizes MSMEs, Enhancing Global Financial Transparency: AIS Merevolusi UMKM, Meningkatkan Transparansi Keuangan Global - Musdalifah, Siti; Hariyanto, Wiwit (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of Accounting Information Systems (AIS) on decision-making processes' transparency and accountability in Micro, Small, and Medium Enterprises (MSMEs), focusing on Frozen Food Arsid in Krian District, Sidoarjo. Employing a qualitative approach, data was gathered through interviews and documentation analysis. Results indicate that AIS implementation positively influences transparency and accountability in financial reporting, affecting employee performance. The findings highlight the significance of AIS in enhancing MSMEs' financial practices, providing practical insights for stakeholders to improve decision-making processes and organizational performance, ultimately contributing to economic sustainability. Highlights: AIS boosts MSMEs' transparency and accountability. Qualitative data collection method employed. Findings underscore AIS's pivotal role in decision-making processes. Keywords: AIS, Transparency, Accountability, MSMEs, Decision-making